Impact of social ties on self reported health in France: Is everyone affected equally? - Wilkinson Richard G; Heritage Zoë; Grimaud Olivier; Pickett Kate E (BMC, 2008)
Abstract Aim To examine the association of social ties and income with self reported health, in order to investigate if social ties have a greater impact on the health of people on low incomes compared to those financially better off. Methods A nationally representative cross-sectional study of 5205 French adults using data from questionnaires which asked about health, income and relationships with family and friends etc. Results Less than good self-rated health (SRH) is twice as frequently reported by people in the lowest income group than those in the highest income group. People with low incomes are also more likely to have felt alone on the previous day, received no phone call during the last week, have no friends, not be a member of a club, and to live alone. Socially isolated people report lower SRH. Likelihood ratio tests for interaction vs. main effect models were statistically significant for 2 of the measures of social ties, borderline for 2 others and non-significant for one. For 4 of the 5 indicators of social ties, larger odd ratios show that social isolation is more strongly associated with less than good SRH among people on low incomes compared to those with a higher income. Conclusion Social isolation is associated with 'less than good' self-rated health. This effect appears to be more important for people on a low income.